Kajian Tafsir Munir Karya Wahbah Az-zuhayli - Moch. Yunus (HUMANISTIKA : Jurnal Keislaman, 2018)
This paper examines the exegesis of al-Munir by Wahbah az-Zuhayli, Tafsir al-Munir is a classical commentary packed with contemporary language and combines the classical interpretive orientalist and the beauty of his interpretation so easily understood. This commentary is written because the Wahbah is concerned over the view of the classical commentary that offers no solution to contemporary problems. The method used is the tahlili method whose interpretation at the beginning of each letter takes precedence over the virtue and the contents of the letter. And his tafsir style combines the interpretation of bi al-Ra'yi and the interpretation bi al-Riwayah. In tafsirnya there are two aspects of aspects of worship and the second aspect of muamalat.